Female Online Motorcycle Drivers and Their Gender Equity: A Case in Pontianak - Adinda Mursalina; Agustina Milda; Mirdasila Mirdasila; Dahniar Th Musa; Annisa Rizqa Alamri; Marini Marini (Journal of Feminism and Gender Studies, 2023)
Online motorcycle taxi is a media in the form of an online application as a tool to order transportation services. Customers use gadgets to order motorcycle taxis online and connect with drivers who are ready to take or pick them up to their desired destination. The emergence of online motorcycle taxi drivers has caused a dynamic in viewing human work so that not only men can work as online motorcycle taxi drivers. This article aims to prove that women as online motorcycle taxi drivers is a form of gender equality. This study used a qualitative research method with data analysis techniques using triangulation, and a detection method using a research approach with interviews involving direct interaction between researchers and respondents to obtain information and data based on a frame of mind using ecofeminism. The patriarchal mindset causes a negative view of women and nature, which are seen as objects that can be controlled by men. In this context, ecofeminism offers a solution by strengthening the position of women and nature and fighting for gender equality and environmental protection. In the case of women's online motorcycle taxis, Ecofeminism Theory highlights the potential for gender to be improved by giving equal opportunities and access to women to become online motorcycle taxi drivers, without being limited by gender stereotypes that hinder women's roles. The results of this study show that as online motorcycle taxi drivers, women are able to make money, make decisions and develop the same potential as men while reducing the stereotype that online motorcycle taxi drivers work only for men. Keywords: Feminism; Women's Existence; Ojek Online.